Physicochemical and sensorial characterization of honey spirits - Anjos, O. (2019)
Distilled spirits are usually made from fermented sugar-based materials, such as wines or fermented fruits, but other products can be used, namely berries or honey. In this work, an evaluation of honey spirits is done based on its physicochemical and sensory characteristics. Fourteen honey spirit samples of different brands of honey spirit were purchased at the market and from artisan Portuguese producers. Several analytical determinations, namely alcoholic strength, dry matter, density, total acidity, chromatic characteristics, methanol, acetaldehyde, ethyl acetate and higher alcohols were done to characterize all samples. The results pointed out several differences in physicochemical composition of samples. In general, these drinks are characterized by an alcohol strength between 37.4% and 53.0% and a low methanol content, quite null for most samples. Samples with higher ethanol content corresponded to the artisanal samples. Significant differences (p < 0.05) were also observed in the volatile composition and chromatic characteristics suggesting different production technologies. A first list of sensory attributes was obtained for this beverage. Therefore, further research must be done in order to characterize this spirit drink, which has gained market value.